Group names for herbal medicines: the need for introduction and rationale for establishing - M. N. Lyakina; E. L. Kovaleva; O. B. Nikolaeva; N. M. Krutikova; N. G. Olenina; L. A. Kolganov (Регуляторные исследования и экспертиза лекарственных средств)
The article considers the importance of International Nonproprietary Names (INNs) and group names in the development of common information standards for the industry in the light of creation of the EurAsEC market and shared information space. The necessity to define the rules for assigning group names to herbal drugs results from the requirement introduced to Federal Law No. 61-FZ «On circulation of medicines», making it obligatory to specify group names on drug labels in the absence of INNs in the State Register of pharmaceutical products. The article covers the development of the methodological approach to establishing group names for the mentioned group of medicinal products.